Dynamics in detection of markers of viral hepatitis B and C among blood donors and patients as an indicator of the quality of blood donor selection - A. O. Salamanina; O. V. Yunatska; I. A. Tretiakova (Ukrainian Journal of Cardiovascular Surgery, 2018)
An important issue of the safety of donor’s blood is the spread of infections transmitted during blood transfusion, including viral hepatitis B and C. The results of testing donors and patients for markers of viral hepatitis B and C conducted at the UCCC’s Department of Transfusion Control during the period from 2013 until 2015 are presented. The research was done using IHL-analysis and ELISA. The material for the retrospective study was serum taken from 22,144 blood donors and patients, including 9090 samples taken from regular donors, 1,450 samples taken from individuals who wanted to become donors and 11,604 blood samples taken from patients. Tests of 23 samples (0.22%) of donors were found to be positive for HCV-antibodies, and tests of 6 samples (0.057%) were found to be positive for hepatitis B surface antigen. Identification of markers of hepatitis C among donors shows a stable downward trend. The frequency of detection of HBsAg in regular blood donors remains low, and the frequency of detection of HBsAg in individuals who want to become donors decreases.